Interacción social, cultura y prevalencia de anemia infantil en un distrito limeño (2017-2021) - León Pretel, Pricila (2023)
The research «Social interaction, culture and prevalence of childhood anemia in a district of Lima (2017-2021)» was carried out in the district of San Martín de Porres. The main objective was to describe and explain the socio-family factors that affect the generation and prevalence of anemia in children from 6 to 35 months. The method has been mixed; 320 surveys and 5 life stories were applied. The information has been processed in the Statistical-Informatics Program SPSS (version 25). Main results, 80.31% of children had mild or acute anemia, the age of 60% of the mothers ranged from 18 to 29 years, 54% of them have only studied secondary school, 72% come from the coast, 72% do not work outside the home, 41% of families have an income of 930 soles per month, 22% less than 930, 21% an income of 1,000 soles and 17% equal to or greater than 1500.00. 51% of families share the family pot with more than 5 people, 56.56% are cohabitants, 28.44% single mothers and 48.13% live alone. The social conditions and the culture of mothers, with anemic children, are determining factors to prevent and restore them from said disease.